Metode Drill dalam Meningkatkan Keterampilan Membuat Tas Makrame untuk Anak Tunarungu di SLB Bina Bangsa - Salma, Yuliza; Fatmawati, Fatmawati (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2019)
This study discusses vocational skills in making makrame bags for deaf children. This research is a classroom action research. The aim is to improve the ability of children to make makrame bags and to determine the effectiveness of the drill method for learning in the classroom. The research method used is class action research that is to improve teacher performance through the e drill method. This research consists of cycle I and cycle II. in the initial condition of the child 33%, this is because it has not been given maximum training, so the researcher uses the drill method. in the first cycle the first meeting of the child obtained 42%, the second meeting 66%, the third meeting 75% and the fourth meeting 83% but in the core part of the child still needed help so it needs to be continued for the second cycle. both students get 83%, the third meeting gets 91%, at the last meeting students reach 91%, so proven by the drill method can increase the ability of deaf students to know the process of making makrame bags.